PENEGAKAN KODE ETIK DAN DISIPLIN TERHADAP ANGGOTA POLRI YANG MELAKUKAN TINDAK PIDANA OLEH SEKSI PROFESI DAN PENGAMANAN (Studi Pada Seksi Profesi dan Pengamanan Polres Pasaman Barat) - Keling Dapit (LPPM Universitas Ekasakti Padang, 2022)
The Police Code of Ethics and Discipline is a guideline how to act and the behavior of Polri personnel as stated in Article 18 paragraph (2) of Law Number 2 of 2002 concerning the Indonesian National Police. In its implementation, it is undeniable that there has been wrong behavior by members of the National Police, so it is necessary to enforce a code of ethics and discipline by the Provos Unit at the Polres level as regulated in Article 12 paragraph (2) of Perkap Number 2 of 2021 concerning Organizational Structure and Work Procedures at the Resort Police Level. And the Sector Police. This is because the behavior of violating the code of ethics and discipline carried out by members of the National Police in addition to having an impact on the internal police also affects public trust. the enforcement of the code of ethics and discipline against members of the police who commit criminal acts by the profession and security section is carried out after completing the criminal justice process, by holding a KEPP trial to determine sanctions for suspected violators including forms of criminal acts committed related to the subsequent membership status of the Police. the obstacles in enforcing the code of ethics and discipline by the professional section and securing the members of the National Police who commit criminal acts include internal obstacles, namely if PTDH is carried out there will be a shortage of personnel at the West Pasaman Police. Furthermore, the external constraint is that if PTDH is not carried out, it will adversely affect public trust in the Polri institution. the efforts of the profession and security section in overcoming obstacles to enforcement of the code of ethics and discipline against members of the police who commit criminal acts are in imposing sanctions on suspected violators being given the opportunity to remain as members of the National Police and monitoring by the Provos Unit in order to foster suspected violators to comply with the disciplinary regulations of members. Polri as stipulated in Government Regulation Number 2 of 2003 concerning Disciplinary Regulations for Members of the Indonesian National Police.